Spermine accumulation via spermine synthase promotes tumor cell proliferation in head and neck squamous cell carcinoma - Xi Chen; Fei Song; Peng Xiao; Yisong Yao; Dongxian Li; Yuhui Fang; Shijun Lv; Yakui Mou; Yumei Li; Xicheng Song (BMC Cancer)
Abstract Background Head and neck squamous cell carcinoma (HNSCC) is among the most aggressive malignancies, underscoring the need for early diagnosis to improve patient outcomes. Tumor-derived exosomes, which can be non-invasively obtained and reflect the metabolic state of tumors in real-time, are under increasing investigation for their diagnostic potential. Herein we analyzed metabolite differences in exosomes, serum, and tissues from patients with HNSCC to identify potential diagnostic biomarkers of clinical relevance. Methods Non-targeted metabolomics based on liquid chromatography–mass spectrometry was employed to quantify metabolites in exosome, serum, and tissue samples from 11 patients with HNSCC and six patients without cancer. The metabolic profiles of HNSCC were analyzed through univariate and multivariate statistical methods, differential metabolite analysis, and pathway enrichment analysis. Results We identified three differential metabolites in exosomes, 45 in serum, and 33 in tissues. Notably, patients with HNSCC exhibited significant disruptions in protein and amino acid metabolism. Spermine was exclusively detected in exosomes and tissues from patients with HNSCC. We hypothesize that spermine is extracellularly secreted by malignant cells via exosomes and subsequently enters the bloodstream. Moreover, spermine synthase was highly expressed in HNSCC tissues. Knocking down spermine synthase markedly impaired HNSCC cell proliferation and migration. Conclusions This study provides a preliminarily characterization of the metabolic profile of HNSCC and highlights spermine and its synthetic pathways as potential diagnostic and therapeutic targets. Future studies are warranted to elucidate the mechanism of action of spermine in HNSCC and explore its utility in early diagnosis and therapeutic development.